2017
DOI: 10.1021/acsami.7b07947
|View full text |Cite
|
Sign up to set email alerts
|

Significant Enhancement of Thermal Conductivity in Polymer Composite via Constructing Macroscopic Segregated Filler Networks

Abstract: The low efficiency of thermal conductive filler is an unresolved issue in the area of thermal conductive polymer composites. Although it is known that minimizing phonon or electron interfacial scattering is the key for achieving high thermal conductivity, the enhancement is generally limited by preparation methods that can yield the ideal morphology and interfaces. Herein, low temperature expandable graphite (LTEG) is added into a commercial impact modifier (Elvaloy4170), which is then coated onto poly(butylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…Figure e elaborates that for the maxima of SE and Kmax, the system needs to be optimized in terms of the number of particles of fillers and this optimum ratio depends upon the dimensional parameters of the fillers and the total volume fraction of the fillers. Such high thermal conductivities of more than 5 W/mK in polymer matrix composites using graphite based fillers have been recently reported not only by researchers but also by the polymers compounding industries .…”
Section: Parametric Studiesmentioning
confidence: 73%
“…Figure e elaborates that for the maxima of SE and Kmax, the system needs to be optimized in terms of the number of particles of fillers and this optimum ratio depends upon the dimensional parameters of the fillers and the total volume fraction of the fillers. Such high thermal conductivities of more than 5 W/mK in polymer matrix composites using graphite based fillers have been recently reported not only by researchers but also by the polymers compounding industries .…”
Section: Parametric Studiesmentioning
confidence: 73%
“…Amongst these design strategies, the dip-coating of the conductive nanoparticles on the surface of polymer-based substrate has been in growing demand for fabricating flexible piezoresistive sensors. Previous studies showed that this strategy can be achieved through a scalable, low-cost processing technology [ 25 , 32 , 33 , 34 ]. In addition, commercial sponges proved to be ideal candidates for the three-dimensional (3D) porous structure used in preparing high-performance piezoresistive sensors via the dip-coating process [ 35 , 36 ]; while polydimethylsiloxane (PDMS), as a thermosetting polymer with good flexibility and elasticity, has been in demand for improving the compressibility of pressure sensors.…”
Section: Background Studymentioning
confidence: 99%
“…Generally, high TC polymer composites are formulated by compounding high TC fillers with polymer matrix . During the past decades, ceramic‐based fillers such as aluminum oxide (Al 2 O 3 , 30 Wm −1 K −1 ), aluminum nitride (AlN, 170‐220 Wm −1 K −1 ), silicon carbide (SiC, 120 Wm −1 K −1 ), and boron nitride (BN, 380 Wm −1 K −1 ) have been widely applied to improve the TC performance of polymer composites without deteriorating the electrical insulation performance . However, it is hard to improve the TC performance of polymer composites through simple mixing high TC fillers with polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] During the past decades, ceramic-based fillers such as aluminum oxide (Al 2 O 3 , 30 Wm −1 K −1 ), aluminum nitride (AlN, 170-220 Wm −1 K −1 ), silicon carbide (SiC, 120 Wm −1 K −1 ), and boron nitride (BN, 380 Wm −1 K −1 ) have been widely applied to improve the TC performance of polymer composites without deteriorating the electrical insulation performance. [12][13][14][15][16][17] However, it is hard to improve the TC performance of polymer composites through simple mixing high TC fillers with polymers. Great efforts have been made to fabricate high TC composites through fillers orientation, hybrid and modification method.…”
Section: Introductionmentioning
confidence: 99%